Strategies to address gaps in the supply and demand of skills and knowledge in built environment-related disciplines - Keraminiyage, Kaushal; Lill, Irene (International Journal of Strategic Property Management, 2013)
“Strategies to address gaps in the supply and demand of skills and knowledge in built environment-related disciplines” International Journal of Strategic Property Management, 17(2), p. 111-113.First Publish Online: 27 Jun 2013